Evaluation of Land Suitability for Sustainable Maize Crops in Popayato District, Pohuwato Regency - Wirdawati Nusi; Yulistia Lakoro; Saptan Gobel; Moch. Rio Pambudi; Sunarty Suly Eraku (Journal of Multidisciplinary Science, 2024)
Utilisation of land resources requires information on the potential and limitations of land use so that commodities to be cultivated can achieve optimal results. This study aims to determine the suitability of land for corn (Zea mays L.) in Popayato District, Pohuwato Regency. This research uses a qualitative method that combines a statistical analysis approach with spatial analysis techniques. Results pH, texture, effective depth, organic C-C, clay CEC, temperature, rainfall, drainage, slope, altitude, and erosion. The maize crop requires an optimum temperature between 26°C and 807-1200 mm of rainfall annually, which is a uniform distribution of rainfall. The soil has a texture of loam, dusty loam, or sandy loam which is ideal for maize growth and development. Maize requires sufficient aeration so that the plant roots can absorb nutrients well. The soil drainage is good and the growth rate is quite fast.